Risk assessment of acquiring listeriosis from consumption of chicken offal in Selangor, Malaysia - Kuan, Chee Hao (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Listeria monocytogenes (L. monocytogenes) is an important foodborne pathogen which can cause foodborne listeriosis with high mortality rates especially in susceptible population groups such as pregnant women, elderly and immunocompromised individuals. The biosafety level of L. monocytogenes in chicken offal has becomes a great concern as chicken offal is a cheap source of protein and it is often served as side dishes in South East Asian countries. In Malaysia, the consumption of chicken offal has almost doubled from 5 g per capita per day in the early 1980s to 9 g per capita per day in 2009. In this study, risk assessment was conducted to estimate the risk of acquiring listeriosis from consumption of chicken offal in Malaysia. A microbial survey on the prevalence and concentration of L. monocytogenes in chicken offal were carried out in Selangor, Malaysia over a one-year period (November 2010 to October 2011). It was assumed that there were no seasonal changes in the prevalence and consumption pattern all year round. Assuming that 5.6 million people in Selangor, Malaysia consume a single serving (125 g) of chicken offal per week, it is estimated that in a year there could be 0.61 cases and 1.98 × 10-4 cases of listeriosis per 100,000 population of pregnant woman and immunocompromised individual, respectively. However, the potential for getting listeriosis among the healthy population was very low, only 1.39 × 10-8 cases per 100,000 population. This study demonstrated risk assessment model not only used as a tool to estimate the risk of acquiring illness but it can influence public health surveillance and providing data in setting appropriate level of protection.